METHOD OF RE-ELIMINATION OF COMPLICATIONS AFTER URETHROPLASTY IN CHILDREN - X.N. Xotamov; Nasirov; F.F. Bayaxmedov; X.X. Xudaynazarov (Western European Studies, 2024)
to achieve good results using the method of balapenial neouretroplasty with the method of “Vesicoendopunction” in the repeated operation of patients with hypospadias observed
Keywords: TashPMI; patients; hypospadias